HUBUNGAN PENGETAHUAN TENTANG ANEMIA DENGAN KEPATUHAN MENGKONSUMSI TABLET TAMBAH DARAH REMAJA PUTRI DI SMA NEGERI 1 KARANGANOM - Astri Wahyuningsih; Anna Uswatun (INVOLUSI: Jurnal Ilmu Kebidanan, 2019)
Anemia is a medical condition in which the number of red blood cells or hemoglobin is less than normal. According to the Indonesian Ministry of Health in 2016, the target coverage of giving iron tablets for adolescent girls is 30% by 2019. Compliance is the extent to which patient behavior is in accordance with the provisions given by health professionals. Efforts to overcome anemia in adolescents include increasing knowledge to increase compliance with iron tablets. This study aims to determine the relationship between knowledge of anemia and adherence to consuming blood supplement tablets for female adolescents in SMA Negeri 1 Karanganom. This research method is descriptive quantitative with cross sectional approach. The population of this study were 41 students of class XI IPS 1 and XI IPS 2 who attended SMA Negeri 1 Karanganom with a total of 41 respondents using a purposive technique. The instruments used were questionnaires and observation sheets. Data were analyzed using univariate and bivariate tests. The result of the study was that there was a correlation between knowledge about anemia and adherence to consuming blood-supplemented tablets for girls at SMA Negeri 1 Karanganom with a result of 0.000 (p <0.05). The conclusion of this study is the level of knowledge about anemia in class XI adolescent girls at SMA Negeri 1 Karanganom is sufficient. The level of compliance with iron supplement consumption was non-adherent. There is a relationship between knowledge about anemia and compliance with iron supplement consumption.